EWSR1 translocation in primary hyalinising clear cell carcinoma of the thymus. Issue 3 (19th July 2019) - Porubsky, Stefan; Rudolph, Birgit; Rückert, Jens‐Carsten; Küffer, Stefan; Ströbel, Philipp; Roden, Anja C; Jain, Deepali; Tousseyn, Thomas; Van Veer, Hans; Huang, James; Antonicelli, Alberto; Kuo, Tseng‐tong; et al.
Abstract : Aims: In thymic carcinomas, focal clear cell change is a frequent finding. In addition to a prominent, diffuse clear cell morphology, some of these carcinomas show an exuberant hyalinised extracellular matrix, and therefore probably represent a separate entity. However, a characteristic genomic alteration remains elusive. We hypothesised that, analogous to hyalinising clear cell carcinomas of the salivary gland, hyalinising clear cell carcinomas of the thymus might also harbour EWSR1 translocations. Methods and results: We identified nine archived cases of thymic carcinoma with focal clear cell features and two cases that showed remarkable hyalinised stroma and prominent, diffuse clear cell morphology. These two cases expressed p40 and were negative for Pax8, CD5, and CD117. Programmed death‐ligand 1 was highly positive in one case (70%), and negative in the other one. EWSR1 translocation was identified in both cases of hyalinising clear cell carcinoma, and was absent in all nine carcinomas that showed clear cell features without substantial hyalinisation. In one of the EWSR1 ‐translocated cases, a fusion between exon 13 and exon 6 of EWSR1 and ATF1, respectively was identified by next‐generation sequencing. Conclusions: These findings suggest that the EWSR1 translocation and possibly the EWSR1–ATF1 fusion might be unifying genomic alterations for thymic clear cell carcinomas with prominent hyalinised stroma, for which we propose the term 'hyalinising clear cell carcinoma of the thymus'. Because the immunophenotype is unspecific, testing for the EWSR1 translocation might be helpful in discriminating this entity from other thymic neoplasms or metastases, in particular those with clear cell change.